Analisis Faktor-Faktor yang Mempengaruhi Harga Emas di Indonesia Periode 2023–2025 - Amelia Riski Cahya Ningrum; Yosi Safri Yetmi; Umi Kulsum (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study aims to analyze the factors influencing gold prices in Indonesia during the 2023–2025 period. The research employed a quantitative method with an associative approach to examine the relationship between macroeconomic variables and gold prices. The study utilized secondary data obtained from Bank Indonesia, Statistics Indonesia, the Indonesia Stock Exchange, and Investing.com. Panel data regression analysis was applied to determine the effect of each independent variable on gold prices. The variables examined included inflation, gross domestic product (GDP) per capita, interest rates, the rupiah exchange rate, the Indonesia Composite Stock Price Index (IDX Composite), and the unemployment rate. The findings indicate that, partially, inflation and the IDX Composite have a positive but insignificant effect on gold prices. GDP per capita and the unemployment rate have a negative but insignificant effect on gold prices. In contrast, interest rates have a negative and significant effect on gold prices, while the rupiah exchange rate has a positive and significant effect on gold prices. Simultaneously, all six independent variables have a significant influence on gold prices in Indonesia during the 2023–2025 period. These findings suggest that changes in macroeconomic conditions collectively play an important role in influencing gold price movements and may serve as valuable considerations for investors and policymakers in making economic and investment decisions.